2020
DOI: 10.1021/acsbiomaterials.0c00660
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Fmoc-Arg-Phe-Phe Peptide Gels with Highly Potent Bactericidal Activities

Abstract: The emergence of antibiotic resistance and the increasing rate of bacterial infections have motivated scientists to explore novel antibacterial materials and strategies to circumvent this challenge. Gels fabricated from ultrashort self-assembled peptides have turned out to be the most promising bactericidal materials. Self-assembled Fmoc-Phe-Phe gels have been extensively investigated earlier, and it has been shown that these gels possess potent bactericidal properties but suffer from disadvantages, such as po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…[27][28][29] Hydrogels have been established as effective biomaterials for treating infections and wound dressing. [30][31][32] Single amino acids Fmoc-F 33 and Fmoc-L 34 have shown antibacterial activity against Gram-positive bacteria when mixed to form hydrogel co-assemblies. However, no activity was reported against Gram-negative bacteria P. aeruginosa and E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Hydrogels have been established as effective biomaterials for treating infections and wound dressing. [30][31][32] Single amino acids Fmoc-F 33 and Fmoc-L 34 have shown antibacterial activity against Gram-positive bacteria when mixed to form hydrogel co-assemblies. However, no activity was reported against Gram-negative bacteria P. aeruginosa and E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogel completely recovered its initial moduli after four cycles, indicating good self-healing ability. In 2020, Singh et al reported an Fmoc-capped tripeptide composed of a popular dipeptide motif, PhePhe in the D form, owing to its high proteolytic stability and tendency for enhanced gelation, and a cationic amino acid Arg or His in L-form because of the potent bactericidal activities ( Figure 9 H, Table 4 ) [ 115 ]. These peptides displayed self-assembled fibrillar morphology with thixotropic behavior.…”
Section: Tripeptide (T 3 P)-based Thixotropic Hydr...mentioning
confidence: 99%
“…( K ) Self-healing test of macroscopic hydrogels; reproduced with permission from Ref. [ 115 ]. Copyright (2020) American Chemical Society.…”
Section: Figures Scheme and Tablesmentioning
confidence: 99%
“…Fmoc-Tyr-Tyr-NH 2 (YY), Fmoc-Trp-Trp-NH 2 (WW), and Fmoc-Trp-Trp-His-NH 2 (WWH) were synthesized following the protocol reported by our group earlier. 31 Standard 9-fluorenylmethoxycarbonyl (Fmoc)-based SPPS method was employed using the Rink amide AM resin as a solid support. Fmoc-protected amino acids (3 equiv.)…”
Section: Synthesis Of Di-and Tripeptidesmentioning
confidence: 99%